Computer Assisted/Aided Language Learning - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2005)
This entry provides a thorough introduction to computer- assisted and -aided language learning (CALL). It starts by providing the definition and history of CALL and associated relevant terms. Then, an existing CALL methodological framework is presented and discussed. This is then followed by an overview of the current state of CALL by citing some representative examples of its uses and discussing advantages and disadvantages of current CALL systems. The chapter concludes with a discussion of present and future research and commercial directions of CALL.